Annotated list of ichthyofauna of inland and coastal waters of Sakhalin Island. 2. Families Osmeridae-Scombropidae - Dyldin, Yury V.; Orlov, Alexei M. (Journal of Ichthyology, 2021)
The second part of the report represents the annotated list of fish species found in the marine (within a 200-mile zone), brackish, and fresh waters of Sakhalin: 139 species from 22 orders, 54 families, and 105 genera.